2017
DOI: 10.1111/rssb.12228
|View full text |Cite
|
Sign up to set email alerts
|

Random-projection Ensemble Classification

Abstract: We introduce a very general method for high dimensional classification, based on careful combination of the results of applying an arbitrary base classifier to random projections of the feature vectors into a lower dimensional space. In one special case that we study in detail, the random projections are divided into disjoint groups, and within each group we select the projection yielding the smallest estimate of the test error. Our random-projection ensemble classifier then aggregates the results of applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 129 publications
(158 reference statements)
3
135
0
Order By: Relevance
“…Numbers after the abbreviations mean the training set of size of n (a subsample of the data), and then, the remaining data formed the test set. ES k NN, ensemble of subset of k NN classifiers; GP, Gaussian process; k NN, k ‐nearest neighbors; LDA, linear discriminant analysis; NSC, nearest shrunken centroids; OTE, optimal tree ensemble; PenLDA, penalized LDA; QDA, quadratic discriminant analysis; RF, random forest; RP, random projection; SRD, sum of ranking differences; SVM, support vector machine; the number after the abbreviations means “sufficient dimension reduction (SDR5) assumption”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numbers after the abbreviations mean the training set of size of n (a subsample of the data), and then, the remaining data formed the test set. ES k NN, ensemble of subset of k NN classifiers; GP, Gaussian process; k NN, k ‐nearest neighbors; LDA, linear discriminant analysis; NSC, nearest shrunken centroids; OTE, optimal tree ensemble; PenLDA, penalized LDA; QDA, quadratic discriminant analysis; RF, random forest; RP, random projection; SRD, sum of ranking differences; SVM, support vector machine; the number after the abbreviations means “sufficient dimension reduction (SDR5) assumption”…”
Section: Resultsmentioning
confidence: 99%
“…Cannings and Samworth recently introduced a new technique called “random‐projection ensemble classifier” (RPEC). The authors introduced a general framework for high‐dimensional classification on carefully selected low‐dimensional random projections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the case of random forests, each ξ i encodes the points in D * i , as well as randomly chosen sets of features used for training T i . More generally, the representation (1.2) is relevant to other types of randomized ensembles, such as those based on random rotations (Blaser and Fryzlewicz, 2016), random projections (Cannings and Samworth, 2017), or posterior sampling (Ng and Jordan, 2001;Chipman et al, 2010).…”
Section: Background and Setupmentioning
confidence: 99%
“…Algorithms based on random projections have recently been shown to be highly effective for several different problems in high dimensional statistical inference. For instance, in the context of high dimensional classification, Cannings and Samworth () showed that their random projection ensemble classifier that aggregates over projections that yield small estimates of the test error can result in excellent performance. Marzetta et al .…”
Section: Introductionmentioning
confidence: 99%